The Impact of Audit Firm Size, Auditor Independence and Financial Expertise on Earning Quality: Mediating Role of Audit Quality - Aziz, Atif; Salman, Syed Muhammad; Hassan, Muhmmad; Younus, Muhammad Kamran; Uddin, Humayun Fareed (iRASD Journal of Economics, 2023)
Earning quality of organization depends upon the audit quality and could be achieved using auditors’ expertise and firm size and this aspect demands the emphasis of new researchers. Hence, the current article investigates the effects of auditors’ independence, audit firm size and auditors’ financial expertise on earning quality of the manufacturing industry in Malaysia. The article also explores the mediating role of audit quality among auditors’ independence, audit firm size, auditors’ financial expertise and earning quality of the manufacturing industry in Malaysia. The study gets the data from the audit department of Malaysian manufacturing companies. The article checks the nexus among variables using smart-PLS. The outcomes revealed that the auditors’ independence, audit firm size and auditors’ financial expertise have a positive association with earning quality. The outcomes also exposed that audit quality significantly mediates among auditors’ independence, audit firm size, auditors’ financial expertise and earning quality of the manufacturing industry in Malaysia. The regulators could get the guidelines to achieve high quality earnings and audits using auditors’ independence and financial expertise.